High intensity sprint training reduces lipid peroxidation in fast-twitch skeletal muscle - Cunningham, P.; Geary, M.; Harper, R.; Pendleton, A.; Stover, S. (Journal of Exercise Physiology online, 2005)
It was hypothesized that oxidative stress could be induced by acute, high intensity exercise and that exercise-induced oxidative tissue damage could be reduced by long-term, high intensity training. Untrained mice engaged in six consecutive 30 s sprints on a rodent treadmill (15° incline) at a pace of 30 m/min. Concentrations of malondialdehyde (MDA), a product of lipid peroxidation and an indicator of oxidative stress, were determined spectrophotometrically in fast- and slow-twitch muscles in the experimental group and in unexercised controls. After the acute exercise, MDA concentration was unaffected in the slow-twitch soleus muscle but was elevated in the fast-twitch extensor digitorum longus (EDL) muscle, indicating an increase in lipid peroxidation. To assess the effects of long-term, high intensity exercise, mice engaged in twice-weekly sprint training sessions (three to six 30 s sprints at a pace of 24-30 m/min on a 5-15° incline) for 12 weeks. Following the training regimen, MDA concentration in the soleus did not differ significantly from untrained control. However, MDA concentration in the EDL was significantly reduced in trained mice, suggesting a decrease in lipid peroxidation.